Análise de tendências e padrões climáticos para a mesorregião do sertão paraibano com ênfase nas energias renováveis - Medeiros, Susane Eterna Leite (2018)
The purpose of this work was to understand the dynamics of climate evolution inherent to the Sertão Paraibano mesoregion, in order to verify the effects of its changes on the potential of electricity production by renewable sources, in particular solar photovoltaic and hydraulic, since these depend on natural resources that may be influenced by climatic conditions. The Sertão Paraibano mesoregion has social, economic and environmental relevance because it contains the state's largest water complex, Coremas-Mãe D'água, used for both the population supply and irrigation and electricity generation by a Small Hydroelectric Plant (SHP). In the study of trends with precipitation data, five meteorological stations were used. The non-parametric Mann-Kendall test was applied to the monthly, quarterly, half-yearly and annual data series for each station. The results indicated a significant tendency of increase for precipitation, observed in four of the five meteorological stations, especially in the annual evaluation, with increments between 2.67 mm/year and 5.45 mm/year. Given the scarcity of meteorological stations with temperature data, data estimated by the Estima_T program for seven localities and data available in two stations maintained by the National Institute of Meteorology (INMET) were used. A low dispersion of the data was obtained in relation to the annual average values, thus, low variability, with the average annual air temperature being between 21.9 ºC (in Teixeira) and 27.8 ºC (in Patos), as expected for regions of semi-arid climate of the Brazilian Northeast. In addition, significant increase trends were observed for mean air temperature in all locations, ranging from 0.008 °C/year to 0.011 °C/year. In view of these climatic changes observed for the Sertão Paraibano mesoregion, it was sought to verify its influence on the potential of energy generation by renewable sources, analyzing the relation between precipitation and the average tributaries and the generation of electricity by the SHP of Coremas. Increases in average air temperature would decrease the efficiency of photovoltaic panels, since the ability to generate electricity depends on its operating temperature. Thus, a direct and significant correlation was observed mainly by comparing the cumulative precipitation in the year of observation together with the two years prior to the production of electricity by SHP. However, the increases observed for precipitation did not influence the electricity production at the plant, due to the prioritization of the multiple uses of the reservoir water. In relation to the potential of photovoltaic solar energy generation, the Sertão Paraibano presented excellent conditions for the implementation of this type of renewable source and the results showed that the electricity generated would be smaller considering for the calculations the last 10 years of average temperature data of the air, ie the most recent data, than if using the oldest data (10 first years) or the complete series. However, this difference was very small and it was possible to conclude that despite the high temperatures recorded and the increases observed from the trend analysis, the potential of energy generation by solar photovoltaic source did not suffer significant changes.